1977
DOI: 10.1677/joe.0.0740143
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Neonatal Androgenization on Luteinizing Hormone, Follicle-Stimulating Hormone, Prolactin and Testosterone Levels in Male Rats

Abstract: It is generally accepted that the administration of androgens to female rats in the neonatal period suppresses cyclic gonadotrophin release and a tonic gonadotrophin release occurs (Barraclough, 1966;Gorski, 1971). The tonic or male gonadotrophin pattern characteristically shows higher levels of plasma and pituitary follicle-stimulating hormone (FSH) and serum prolactin compared with female rats (Johnson, 1967(Johnson, , 1971Kragt & Ganong, 1968;Neill, 1972).In spite of the fact that the neonatal administratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
4
0

Year Published

1977
1977
1990
1990

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 4 publications
3
4
0
Order By: Relevance
“…These results and a previous report [Moguilevsky et at., 1977] indicate that the establishment of sexual dif ferences in the mechanisms of control of FSH is a relevant process that takes place during the differentiation of hypothalamus, and confirm that the devel opment of these mechanisms is directly influenced by the presence of tes tosterone in the first days of life. The fact that neonatal androgenization increased FSH levels in the prepubertal and adult female rats also supports this point of view.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results and a previous report [Moguilevsky et at., 1977] indicate that the establishment of sexual dif ferences in the mechanisms of control of FSH is a relevant process that takes place during the differentiation of hypothalamus, and confirm that the devel opment of these mechanisms is directly influenced by the presence of tes tosterone in the first days of life. The fact that neonatal androgenization increased FSH levels in the prepubertal and adult female rats also supports this point of view.…”
Section: Discussionsupporting
confidence: 92%
“…1967;Gorski, 1971], The tonic or male Gn pattern characteristically shows higher levels of plasma and pituitary follicle-stimulating hormone (FSH) and serum prolactin as compared with females [Johnson, 1967[Johnson, , 1971N eill, 1972]. In a previous paper [Moguilevsky et at., 1977], we demonstrated that the administration of testosterone to male rats during the first days of life produces an increase in the FSH and prolactin levels in the adult as compared with untreated males.…”
mentioning
confidence: 99%
“…In previous papers [8,9] it has been dem onstrated that neonatal androgenization in creases FSH in both male and females rats; these results are confirmed again in this paper. Nevertheless, not only such differences dis appear after castration but also androgenized rats showed lower levels of FSH than the controls in the first few days after gonadectomy.…”
Section: Discussionsupporting
confidence: 90%
“…The tonic or male Gn pattern characteristically shows higher levels of plas ma and pituitary follicle-stimulating hormone (FSH) and serum prolactin [4,5,10]. In pre vious papers [8,9] we demonstrated that the administration of testosterone to male and female rats during the first days of life pro duces an increase in the FSH and prolactin levels in the adult as compared with untreated rats.…”
mentioning
confidence: 97%
“…On the other hand, normal levels of adrenal androgens are only of minor importance for the control of gonadotrophic function (Verjans 8c Eik-Nes 1975) and a dynamic reserve of pituitary LH and FSH appropriate for skeletal age and sex has been demonstrated in adequately glucocorticoid-substituted patients with CAH (Reiter et al 1975;Wentz et al 1976;Klingensmith et al 1976;Cacciari et al 1976). Thus, in female patients with CAH, neonatal exposure to high levels of androgens does not, as in the rat (Pfeiffer 1936;Barraclough 1966;Moguilevsky et al 1977) imprint a pattern of gonadotiophin-release which is permanently different from that seen in normal females.…”
Section: Discussionmentioning
confidence: 91%